2017
DOI: 10.1177/0891243217704631
|View full text |Cite
|
Sign up to set email alerts
|

The Economic and Career Effects of Sexual Harassment on Working Women

Abstract: Many working women will experience sexual harassment at some point in their careers. While some report this harassment, many leave their jobs to escape the harassing environment. This mixed-methods study examines whether sexual harassment and subsequent career disruption affect women’s careers. Using in-depth interviews and longitudinal survey data from the Youth Development Study, we examine the effect of sexual harassment for women in the early career. We find that sexual harassment increases financial stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(164 citation statements)
references
References 60 publications
6
133
0
3
Order By: Relevance
“…Though no personal accounts were put forward in responses to our questionnaire, we know from research in the UK (Phipps, 2018) and on other sectors that women who labour in work that is precarious, low paid and exploitative are also more likely to experience sexual harassment and violence in the workplace (Kensbock, Bailey, Jennings, & Patiar, 2015;Waugh, 2010). Such occurrences have devastating consequences for victims that include severe career disruption and lifelong earning losses (McLaughlin, Uggen, & Blackstone, 2017). Furthermore, the work permit and right to remain structure in Ireland for non-EU workers means that migrant women are particularly vulnerable.…”
Section: What Does Non-status Mean For Gender Equality In Academia?mentioning
confidence: 99%
“…Though no personal accounts were put forward in responses to our questionnaire, we know from research in the UK (Phipps, 2018) and on other sectors that women who labour in work that is precarious, low paid and exploitative are also more likely to experience sexual harassment and violence in the workplace (Kensbock, Bailey, Jennings, & Patiar, 2015;Waugh, 2010). Such occurrences have devastating consequences for victims that include severe career disruption and lifelong earning losses (McLaughlin, Uggen, & Blackstone, 2017). Furthermore, the work permit and right to remain structure in Ireland for non-EU workers means that migrant women are particularly vulnerable.…”
Section: What Does Non-status Mean For Gender Equality In Academia?mentioning
confidence: 99%
“…Baker observed that female general practitioner colleagues subjected to sexual harassment, whether from colleagues or patients, had ‘withdrawn from their full scope of practice’, diminishing their earning potential and services they offered to their patients . In addition, mental‐health sequelae of depression, anxiety and substance misuse may persist for up to a decade after the abuse . Furthermore, victims often exhibit low self‐esteem, self‐blame, and interpersonal relationship problems…”
Section: The Scale Of the Problemmentioning
confidence: 99%
“…A non‐progressive workplace culture facilitates ostracisation of victims who speak out, thus calling for a culture change initiated by employers . In turn, the economic cost of work withdrawal, such as sick leave or job vacating, may be reduced .…”
Section: The Legal Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual harassment continues to be a 'systemic trauma' (Fitzgerald, 2017) for women in the workplace, with consequences for victims that include depression (Friborg et al, 2017;Houle, Staff, Mortimer, Uggen, & Blackstone, 2011), burnout (Takeuchi et al, 2018), anxiety (Mushtaq, Sultana, & Imtiaz, 2015) and even post-traumatic stress disorder (Avina & O'Donohue, 2002;see Chan, Lam, Chow, & Cheung, 2008, or Sojo, Wood, & Genat, 2016, for meta-analyses and a review of health effects). All of this is in addition to the effects on women's careers: harassment may make them more likely to quit jobs, even when doing so is economically disadvantageous (McLaughlin, Uggen, & Blackstone, 2017), with long-term economic effects.…”
Section: Introductionmentioning
confidence: 99%